PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI PENJUALAN, PEMBELIAN DAN PERSEDIAAN BERBASIS WEB (STUDI KASUS ARI JAYA MOTOR CIPARAY) - Anggreini, Novita Lestari; Andiva, Anindita Nur (Journal of Economics, Accounting, Tax, and Management (JECATAMA); Vol 2 No 1 (2023): JECATAMADO - 10.70428/jecatama.v2i1.673, 2023)
This Final Project is entitled "Design and Implementation of Web-Based Sales, Purchase and Inventory Information System (Case Study Of Ari Jaya Motor Ciparay)" which aims to analyze, design, implement and test sales, purchasing and inventory information systems at Ari Jaya Motor Ciparay. The research method used is descriptive method, this method explains the reality that occurs based on facts sourced from primary data and secondary data and uses qualitative and quantitative data types. The data collection methods used are observation, interviews, and literature study. The design of this information system uses a web programming language with PHPMyAdmin and Mysql databases. The system development method used is the waterfall method using a systematic approach, starting from analysis, design, testing and implementation, as well as testing this system using the black box method. The information system that has been created for Ari Jaya Motor Ciparay can be a solution to the problems that occur, as well as a tool in the process of selling and purchasing transaction activities as well as inputting goods data, resulting in sales, purchases and inventory reports that can overcome recording problems, stock items uncontrolled, difficulty in finding items that can be overcome with this information system. In addition, this information system has control of access rights on the login menu which functions to protect data security, because the main menu displayed for each user will be different. So it can be concluded, the web-based sales, purchasing and inventory information system has been running well.